1999
DOI: 10.1128/cdli.6.4.519-524.1999
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Capsular Polysaccharide Preparations May Contain Non-C-Polysaccharide Contaminants That Are Immunogenic

Abstract: We measured the capacity to opsonize Streptococcus pneumoniae serotype 6B and estimated the concentration of immunoglobulin G anti-6B capsular polysaccharide (PS) antibodies in 25 pre- and postimmune sera from adults immunized with a pneumococcal PS vaccine. We first studied two postvaccination serum samples displaying less opsonophagocytic capacity than expected. The majority of anti-6B antibodies in the two samples reacted with the capsular PSs of several unrelated serotypes (2, 4, 9V, 19F, and 23F) and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Efforts have been made to identify and standardise laboratory correlates of protection that can aid vaccine efficacy trials in the estimation of vaccine‐induced protection. Analysis of sera from adults has shown that detection of antibodies to serotype 14 by ELISA is serotype‐specific, whereas detection of antibodies to other serotypes is hampered by cross‐reactivity [24,25]. These cross‐reactive antibodies are more prevalent in pre‐vaccination sera than in post‐vaccination sera [26], suggesting that the majority of antibodies induced by vaccination with the polysaccharide vaccine are polysaccharide type‐specific or group‐specific [27].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to identify and standardise laboratory correlates of protection that can aid vaccine efficacy trials in the estimation of vaccine‐induced protection. Analysis of sera from adults has shown that detection of antibodies to serotype 14 by ELISA is serotype‐specific, whereas detection of antibodies to other serotypes is hampered by cross‐reactivity [24,25]. These cross‐reactive antibodies are more prevalent in pre‐vaccination sera than in post‐vaccination sera [26], suggesting that the majority of antibodies induced by vaccination with the polysaccharide vaccine are polysaccharide type‐specific or group‐specific [27].…”
Section: Discussionmentioning
confidence: 99%
“…Since the application of ELISA cannot differentiate between poorly functional antibodies with low avidity and the high-avidity antibodies, ELISAs may not be sufficient to determine the functional quality of antibodies. [168][169][170][171] OPKA has been useful for the direct measurement of the protective capacity of antibodies, which function by opsonizing GBS for phagocytosis. 161 The classical OPKA is a tedious procedure for the examination of several serotype-specific OPKA in a large number of samples.…”
Section: Assessment Of Functional Antibodiesmentioning
confidence: 99%
“…In evaluating pneumococcal vaccines, an enzyme-linked immunosorbent assay (ELISA) is commonly used as the measure of vaccine efficacy by quantitating antibodies to serotype specific S. pneumoniae PS in sera ( 9 ). However, the ELISA assays for antibodies to pneumococcal PS were not always specific and cross-reactivity of antibody binding to several serotypes was often observed ( 10 , 11 ). Opsonophagocytic killing assay (OPKA) is an in vitro surrogate assay to test protective efficacy of the pneumococcal vaccines and is often used to complement the ELISA results ( 12 ).…”
Section: Introductionmentioning
confidence: 99%